Influence of Ink Curing in UV LED Inkjet Printing on Colour Differences, Ink Bleeding and Abrasion Resistance of Prints on Textile - Gregor Lavrič; Igor Karlovits; Deja Muck; Eva Petra Forte Tavčer; Urška Kavčič (Tekstilec)
Digital printing techniques are increasingly present in the field of textile printing. Particularly prominent is the inkjet printing technique using water-based inks, UV LED inkjet printing also increasingly being in use. UV LED inkjet is primarily not intended for direct clothing printing; however, it can be used especially as a hybrid solution in the soft signage market. It is a great option for the printers that are not engaged only in textile printing, and want a more versatile print portfolio, extending it to non-clothing textile products, e.g. soft signage and non-wearable products. As these types of products often require colour reproduction of logos, accurate colour reproduction, good ink adhesion and sharpness are important just like in other printing technologies. In order to evaluate the impact of UV LED radiation amount on colour differences, ink bleeding and abrasion resistance, six different fabric samples (five woven and one nonwoven) were printed using a UV LED inkjet printer. Based on the results of colour difference, it was established that a reduction of UV radiation (by half the manufacturer’s recommended amount) had no effect on this parameter. However, perceptible colour differences were observed with the use of different M measurement conditions defined by the international standard ISO 13655-2017. Reducing the amount of UV radiation had no effect on the adhesion and durability of the printed ink. Small differences detected in these two parameters were mainly a consequence of the properties of textile materials and not of decreased UV radiation.